2021
DOI: 10.3390/ijms23010187
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids Seen through the Energy Perspective

Abstract: In all life forms, opposing forces provide the energy that flows through networks in an organism, which fuels life. In this concept, health is the ability of an organism to maintain the balance between these opposing forces, which creates resilience, and a deranged flow of energy is the basis for diseases. Treatment should focus on adjusting the deranged flow of energy, e.g., by the redox modulating activity of antioxidants. A major group of antioxidants is formed by flavonoids, a group of polyphenolic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…Previous studies have reported that B. ceiba flowers contain various bioactive components, such as quercetin, rutin, vitexin, isovitexin, kaempferol, isomangiferin, mangiferin, glucopyranoside, phenyl ethyl rutinoside, protocatechuic acid, chlorogenic acid, methylchlorogenate, and vanillic acid [12], which are phenolic and flavonoid groups. It was previously found that phenolics and flavonoids had antioxidant potential that enhanced the male reproductive system [13][14][15][16], but the B. ceiba stem bark, when extracted at a dose of 1000 mg/kg, had adverse effects on vital organs, including the heart, liver, and kidneys of mice [17]. However, there are limited scientific reports on the biological effects of B. ceiba stamens on the male reproductive system.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that B. ceiba flowers contain various bioactive components, such as quercetin, rutin, vitexin, isovitexin, kaempferol, isomangiferin, mangiferin, glucopyranoside, phenyl ethyl rutinoside, protocatechuic acid, chlorogenic acid, methylchlorogenate, and vanillic acid [12], which are phenolic and flavonoid groups. It was previously found that phenolics and flavonoids had antioxidant potential that enhanced the male reproductive system [13][14][15][16], but the B. ceiba stem bark, when extracted at a dose of 1000 mg/kg, had adverse effects on vital organs, including the heart, liver, and kidneys of mice [17]. However, there are limited scientific reports on the biological effects of B. ceiba stamens on the male reproductive system.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, after decades of research, the exact molecular mechanism responsible for the antioxidant effect of flavonoids is still enigmatic [ 5 , 6 ]. First of all, this is because measuring antioxidant activity appears to be less straightforward than commonly assumed.…”
Section: Introductionmentioning
confidence: 99%
“…Redox energy is essential for life, as it fuels all our biochemical processes [ 1 ]. Most redox energy is safely channeled in the biochemical networks, but for some unknown reason, part of the oxidizing energy flow is uncontrolled [ 2 ].…”
Section: Introductionmentioning
confidence: 99%